2015
DOI: 10.1007/698_2015_355
|View full text |Cite
|
Sign up to set email alerts
|

Historical Land-Use Changes in São Gabriel do Oeste at the Upper Taquari River Basin

Abstract: Agricultural expansion in uplands of the Pantanal in recent decades suppressed a large fraction of native vegetation. In the case of the municipality of São Gabriel do Oeste (SGO), located in the Upper Paraguay River Basin, the processing of historical Landsat imagery indicates from 1984 to 2013 a relative land cover increase in soybean/corn cropland from 25% to 30% and pasture from 17% to 41%, whereas a decrease in native forest from 57% to 28%. These land-use changes produced several outstanding economic ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Moreover, it shows that avulsive processes are commonplace in Pantanal, and changes in land use, particularly in river headwaters in the highlands [44,45], can accelerate the avulsions, making difficult a sustainable use of the Pantanal lowlands.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, it shows that avulsive processes are commonplace in Pantanal, and changes in land use, particularly in river headwaters in the highlands [44,45], can accelerate the avulsions, making difficult a sustainable use of the Pantanal lowlands.…”
Section: Resultsmentioning
confidence: 98%
“…The intense land-use change in the Pantanal highlands during the last four decades also contributes to significant changes in the ecohydrology [40] of the Pantanal. Forest suppression in highlands for crop and livestock [41][42][43][44][45] is responsible for increasing river discharge while reducing evapotranspiration and Water from catchment areas reach the modern depositional lobes through feeder channels confined in meander belts entrenched in the upper fan (IP ¼ intersection point). Abandoned lobes in both systems do not receive water from the catchment nor directly from the feeder channel, and most of the flooding comes from pluvial runoff.…”
Section: Depositional Tract and Surface Hydrology Dynamicsmentioning
confidence: 99%
“…It is extremely important to develop and propose options for the Pantanal including an integral vision in relation to changes in climate and land use (see also Pott and Silva [27] and Buller et al [28]) and their synergic impacts on the Pantanal ecohydrological pulses. Assine [29] has shown that natural changes in the Taquari megafan hydrology were accentuated by the land use in the Upper Taquari Basin.…”
Section: Options For Adaptation and Sustainable Development Under CLImentioning
confidence: 99%
“…On the other hand, Bergier [2] has shown that the runoff/discharge of the rainfall in the uplands has increased due to upland deforestation over the last four decades. As a result, even for less rainy years, the maximum annual flood pulse in Ladário keeps always elevated, usually above 3 m. The upland soil management by agroforestry (see Buller et al [28]) is therefore very relevant for restoring the natural interannual flood pulse dynamics and to improve the resilience of the wetland ecosystems in the lowlands with regard to future climate change risk.…”
Section: Options For Adaptation and Sustainable Development Under CLImentioning
confidence: 99%
“…In the BAP, the slaughterhouse industries intensified their performance, bringing the concept of agribusiness to the new economic contribution of the state of Mato Grosso (IRIGARAY et al, 2011). In Mato Grosso do Sul, mainly in the municipality of São Gabriel do Oeste, between 1984 and 2013, there was a relative increase of 25 to 30% in grain production (soybean and corn), 24% in pasture and a drop of 29% considering the native forest (BULLER et al, 2015(BULLER et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%